Deep learning-based automatic segmentation for size and volumetric measurement of breast cancer on magnetic resonance imaging - Yue, Wenyi; Zhang, Hongtao; Zhou, Juan; Li, Guang; Tang, Zhe; Sun, Zeyu; Cai, Jianming; Tian, Ning; Gao, Shen; Dong, Jinghui; Liu, Yuan; Bai, Xu; et al. (Frontiers in Oncology, 2022)
Purpose: In clinical work, accurately measuring the volume and the size of breast cancer are significant to develop the treatment planning. However, it is time-consuming and exists inter-and intra-observer variations among radiologists. The purpose of this study was to assess the performance of a Res-UNet convolutional neural network based on automatic segmentation for size and volumetric measurement of mass enhancement breast cancer on magnetic resonance imaging (MRI). Materials and Methods: A total of 1000 female breast cancer patients who underwent preoperative 1.5 T dynamic contrast-enhanced MRI prior to treatment were selected from January 2015 to October 2021, and randomly divided into a training cohort (n =800) and a testing cohort (n =200). Compared with the masks named ground truth (GT) delineated manually by radiologists, the model performance on segmentation was evaluated with Dice Similarity Coefficient (DSC) and intraclass correlation coefficient (ICC). The performance of Tumor (T) stage classification was evaluated with accuracy, sensitivity and specificity. Results: In the test cohort, the DSC of automatic segmentation reached 0.89. Excellent concordance (ICC＞0.95) of the maximal and minimal diameter, and good concordance (ICC＞0.80) of volumetric measurement were shown between the model and the radiologists. The trained model took approximately 10-15s to provide automatic segmentation and classified the T stage with an overall accuracy of 0.93; sensitivity of 0.94, 0.94, 0.75 and specificity of 0.95, 0.92, 0.99 respectively in T1, T2 and T3. Conclusions: Our model demonstrated good performance and reliability for automatic segmentation, size and volumetric measurement of breast cancer, which can be time-saving and effective in clinical decision making.